The Chitinous Skeleton of Ianthella basta Marine Demosponge as a Renewable Scaffold-Based Carrier of Antiseptics - Izabela Dziedzic; Kamil Dydek; Alona Voronkina; Valentin Kovalchuk; Teofil Jesionowski; Hermann Ehrlich (Polysaccharides)
The chitinous skeleton of the marine demosponge Ianthella basta exhibits a unique network-like 3D architecture, excellent capillary properties, and chemical inertness, making it highly suitable for interdisciplinary research, especially in biomedical applications. This study investigates the potential of renewable I. basta chitinous scaffolds for drug delivery and wound dressing. The scaffolds, characterized by a microtubular structure, were impregnated with selected commercially available antiseptics, including solutions with hydrophilic and hydrophobic properties. Evaluations against selected clinical strains of bacteria, as well as fungi, demonstrated significant zones of growth inhibition with antiseptics such as brilliant green, gentian violet, decamethoxine, and polyhexanide. Notably, the antibacterial properties of these antiseptic-treated chitin matrices persisted for over 72 h, effectively inhibiting microbial growth in fresh cultures. These findings highlight the considerable potential of I. basta chitin scaffolds as sustainable, innovative biomaterials for controlled drug release and wound dressing applications.